Brain metastasis from gastric adenocarcinoma: A large comprehensive population-based cohort study on risk factors and prognosis - Huang, Lei; Wang, Lei; Shi, Yan; Zhao, Yajie; Xu, Chenying; Zhang, Jun; Hu, Weiguo (Frontiers in Oncology, 2022)
Aims: Although brain metastasis is rare in gastric adenocarcinoma (GaC), it can importantly affects survival and quality of life. This large comprehensive population-based cohort study aimed to investigate factors associated with brain metastasis from GaC, and to explore the time-dependent cumulative mortalities and prognostic factors in patients with GaC and brain metastasis. Methods: Information of patients with GaC diagnosed in 2010 through 2016 was obtained from a large population-based database. Factors associated with brain metastasis were investigated utilizing the multivariable-adjusted logistic regression model. Time-dependent cancer-specific mortalities of patients with GaC and brain metastasis were then computed utilizing the cumulative incidence function (CIF), and mortalities compared across subgroups utilizing Gray’s test. Factors associated with death were further evaluated utilizing the multivariable-adjusted Fine-Gray sub-distribution hazard regression model. Results: Together 28,736 eligible patients were included, who included 231 (1%) cases with brain metastasis and 10,801 (38%) with other metastasis, encompassing 39,168 person-years of follow-up. Brain metastasis occurred more frequently in younger patients (within overall cancers), in cases with gastric cardia tumors, in cases with signet-ring cell carcinoma (within overall cancers), and in those with positive lymph nodes (within overall cancers); it was less often detected in black people. Brain metastasis was associated with more frequent lung and bone metastases. The median survival time of cases with brain metastasis was only 3 months; the 6-month and 12-month cancer-specific cumulative mortalities were 57% and 71%, respectively. Among cases with GaC and brain metastasis, those with gastric cardia cancers (when receiving radiotherapy), those undergoing resection, and those receiving chemotherapy had lower mortality risks, while younger patients (when receiving chemotherapy or radiotherapy) and people with positive lymph nodes (when receiving radiotherapy) had higher mortality hazards. Conclusion: In patients with GaC, brain metastasis was associated with various clinical and pathological factors including age, ethnicity, cancer histology, location, lymph node involvement, and metastases to other sites. Cases with brain metastasis had poor survival which was associated with age, cancer location, lymph node involvement, and management. Our findings offer vital hints for individualized patient care and for future mechanistic explorations.